2004
DOI: 10.1111/j.1471-4159.2004.02765.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage colony stimulatory factor and interferon‐γ trigger distinct mechanisms for augmentation of β‐amyloid‐induced microglia‐mediated neurotoxicity

Abstract: Dysregulated stimulation of microglia, the resident macrophages in the brain, can lead to excessive induction of inflammatory agents and subsequently damage to neurons. Fibrillar b-amyloid peptide (fAb), a major component of senile plaques in Alzheimer's disease (AD) brain, is known to induce microglial-mediated neurotoxicity under certain conditions. Microglial 'priming' by macrophage colony stimulatory factor (MCSF) or interferon-gamma (IFNc) appears to be required for this fAb-induced microglia mediated neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 62 publications
3
37
0
Order By: Relevance
“…Moreover, it was observed that IL-6 secretion was induced only by PrP 106-126 at an early phase (3-6 hr), but Ab 1-40 was more efficient than PrP 106-126 for longer incubation periods, inducing a higher production of this cytokine. In accordance with our results, it was shown that PrP 106-126 induces IL-6 and IL-1b release in cultured mouse microglia (Peyrin et al, 1999;Veerhuis et al, 2002), and fibrillar Ab is unable to induce IL-1 (b and a) release (Li et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, it was observed that IL-6 secretion was induced only by PrP 106-126 at an early phase (3-6 hr), but Ab 1-40 was more efficient than PrP 106-126 for longer incubation periods, inducing a higher production of this cytokine. In accordance with our results, it was shown that PrP 106-126 induces IL-6 and IL-1b release in cultured mouse microglia (Peyrin et al, 1999;Veerhuis et al, 2002), and fibrillar Ab is unable to induce IL-1 (b and a) release (Li et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…Abeta has been reported to increase the generation of ROS by NADPH-oxidase in neurons, microglia, monocytes, neutrophils and astrocytes (58)(59)(60)(61), and apocynin is neuroprotective in cell culture models of AD (62,63). There is convincing evidence suggesting a role for glial cell NADPH oxidase in Abeta-induced neurotoxicity (19,(64)(65)(66)(67).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Lactate Dehydrogenase Activity-LDH enzymatic activity in the culture medium was used to evaluate the extent of cellular damage produced in cultured slices subjected to the different treatments as described previously (34). Briefly, culture medium was collected after incubation of slices, as indicated in the figures, and from the vehicle-treated control cultures.…”
Section: Methodsmentioning
confidence: 99%
“…PAGE and Western Blotting-Immunoblotting was carried out as recently described in detail (31,34). Briefly, slices were homogenized in ice-cold extraction buffer (10 mM triethanolamine, pH 7.4, 1 mM CaCl 2 , 1 mM MgCl 2 , 0.15 M NaCl, 0.3% Nonidet P-40) supplemented with the protease inhibitors pepstatin (2 g/ml), leupeptin (10 g/ml), aprotinin (10 g/ml), phenylmethylsulfonyl fluoride (1 mM), and the phosphatase inhibitor sodium orthovanadate (1 mM).…”
Section: Methodsmentioning
confidence: 99%